Establishment of a spontaneously transformed cell line (JU-PI) from a myxoinflammatory fibroblastic sarcoma - Klaus W Fagerstedt; Tarja Salonen; Fang Zhao; Soili Kytölä; Tom Böhling; Leif C Andersson (Tumor Biology)
Myxoinflammatory fibroblastic sarcoma is a soft-tissue neoplasm most frequently found in the distal extremities of middle-aged adults. Most myxoinflammatory fibroblastic sarcoma are low-grade tumors with propensity for local recurrence after incomplete removal. We report a myxoinflammatory fibroblastic sarcoma which developed in the foot of a 41-year-old male and showed an exceptionally aggressive course with metastatic spread and fatal outcome within 16 months. We managed to establish a spontaneously transformed continuous cell line, called JU-PI, from a metastatic lesion. The JU-PI cells have a sub-tetraploid karyotype including the 1;10 chromosomal translocation and amplification of the proximal end of 3p; these features are considered genetic signatures of myxoinflammatory fibroblastic sarcoma. Both the primary tumor and the JU-PI cells showed nuclear expression of the TFE3 transcription factor but TFE3-activating chromosomal rearrangements were not found. To our knowledge, JU-PI is the first established myxoinflammatory fibroblastic sarcoma cell line. JU-PI cells offer a tool for investigating the molecular oncology of myxoinflammatory fibroblastic sarcoma.